Sistem Pakar Deteksi Awal Covid-19 Menggunakan Metode Certainty Factor - Nasution, Rama Danil Fahri; Hutagalung, Jhonson Efendi; Kifti, Wan Mariatul (Forum Kerjasama Pendidikan Tinggi, 2022)
Data on the development of Covid-19 cases globally and in Indonesia and predictions of an increase in the number of cases, of course, it is necessary to take several steps in dealing with Covid-19, the community must implement physical distancing and maintain personal hygiene and the surrounding environment as preventive measures to suppress the spread of Covid-19. This is in accordance with WHO's appeal regarding strategic steps in dealing with the global Covid-19 pandemic. As in other countries, suspect Corona (people who show symptoms of being infected with COVID-19 and are suspected of having had contact with positive COVID-19 patients) are increasing in Indonesia so that requests for specimen tests at laboratories that have been appointed by the government have also increased. For this reason, another way is needed to detect COVID-19 that is more practical and faster by analyzing data using the Certainty Factor method. With the Covid-19 Early Detection expert system, so that it can provide convenience for Aek Kanopan Regional General Hospital (RSUD) doctors and patients in carrying out the Covid-19 Early Detection process in the database. Can help the Regional General Hospital Doctor (RSUD) Aek Kanopan and provide services to patients in terms of the existing Covid-19 Early Detection and successfully conclude the early symptoms of covid-19 and their handling solutions